2006
DOI: 10.1093/bja/aei266
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of pulse transit time to indicate cardiovascular changes during obstetric spinal anaesthesia

Abstract: PTT measurement gave a beat-to-beat indication of arterial pressure during spinal anaesthesia, and could be developed to allow prediction of the onset of hypotension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 26 publications
(23 reference statements)
3
66
1
2
Order By: Relevance
“…36 More recently, oximeter-based PTT has been used to obtain accurate measurements of changes in blood pressure that occur during induction of general anesthesia as well as to achieve rapid detection of the onset of hypotension in patients undergoing spinal anesthesia for Cesarean delivery. 37,38 While more validation studies are needed, the near instantaneous response time shown in both of these studies is encouraging. 33,34 In aggregate, these data suggest that PTT, at least over short time periods, provides useful information for immediate detection of hemodynamic changes that might be missed if only an oscillometric cuff method is used for periodic blood pressure assessments.…”
Section: Physiology Of the Ppgmentioning
confidence: 84%
“…36 More recently, oximeter-based PTT has been used to obtain accurate measurements of changes in blood pressure that occur during induction of general anesthesia as well as to achieve rapid detection of the onset of hypotension in patients undergoing spinal anesthesia for Cesarean delivery. 37,38 While more validation studies are needed, the near instantaneous response time shown in both of these studies is encouraging. 33,34 In aggregate, these data suggest that PTT, at least over short time periods, provides useful information for immediate detection of hemodynamic changes that might be missed if only an oscillometric cuff method is used for periodic blood pressure assessments.…”
Section: Physiology Of the Ppgmentioning
confidence: 84%
“…This may constitute a problem in certain situations such as when flow redistribution to central parts of the body (heavy injury, temperature etc.) degrades these measurements; another situation where central measurements may prove advantageous is during the presence of strong movements of the peripheral locations which affect pressure measurements [4].…”
Section: Introductionmentioning
confidence: 99%
“…1) Method 1: Sugawara et al [6] showed a linear relationship between percentage changes in instantaneous blood pressure and diameter of the carotid artery. Method 2: According to [3,4,7] there is a non-linear relationship between mean arterial blood pressure ( P) and compliance (ratio of change in volume for a change in pressure), which in turn is related to pulse wave velocity (PWV).…”
Section: Introductionmentioning
confidence: 99%
“…1 However, there is limited understanding in the current literature about the potential use of PTT-related measurement in assessing the ratio of the crural and brachial BP or the ankle brachial index (ABI).…”
mentioning
confidence: 99%